2018
DOI: 10.3324/haematol.2018.195172
|View full text |Cite
|
Sign up to set email alerts
|

The thymidine dideoxynucleoside analog, alovudine, inhibits the mitochondrial DNA polymerase γ, impairs oxidative phosphorylation and promotes monocytic differentiation in acute myeloid leukemia

Abstract: Mitochondrial DNA encodes 13 proteins that comprise components of the respiratory chain that maintain oxidative phosphorylation. The replication of mitochondrial DNA is performed by the sole mitochondrial DNA polymerase γ. As acute myeloid leukemia (AML) cells and stem cells have an increased reliance on oxidative phosphorylation, we sought to evaluate polymerase γ inhibitors in AML. The thymidine dideoxynucleoside analog, alovudine, is an inhibitor of polymerase γ. In AML cells, alovudine depleted mitochondri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…After the tumors became palpable, mice were randomly divided into 4 groups ( n = 5 per group) and treated with vehicle (10% HPBCD in water) or TAK-243 at doses of 10, 15, and 20 mg/kg s.c. BIW for 3 weeks. Mice were weighed and tumor volumes were measured by caliper measurements every 2–3 days using the following equation: tumor volume in mm 3 = tumor length in mm × width 2 in mm × 0.5236 as previously described ( 59 ). At the end of the experiment, mice were euthanized and tumors excised for weighing.…”
Section: Methodsmentioning
confidence: 99%
“…After the tumors became palpable, mice were randomly divided into 4 groups ( n = 5 per group) and treated with vehicle (10% HPBCD in water) or TAK-243 at doses of 10, 15, and 20 mg/kg s.c. BIW for 3 weeks. Mice were weighed and tumor volumes were measured by caliper measurements every 2–3 days using the following equation: tumor volume in mm 3 = tumor length in mm × width 2 in mm × 0.5236 as previously described ( 59 ). At the end of the experiment, mice were euthanized and tumors excised for weighing.…”
Section: Methodsmentioning
confidence: 99%
“…We and others have previously shown that acute myeloid leukemia (AML) cells possess unique mitochondrial characteristics, with increased reliance on oxidative phosphorylation . Knockdown of HTRA2 also disrupted cristae structure in the AML cell line OCI‐AML2 (Figure B).…”
Section: Resultsmentioning
confidence: 76%
“…We found a large number of secondary mutations, including mutations in tumour suppressor and myeloid tumour factor genes as well as transcriptional suppressor and chromatin modifier genes. Besides well‐described mutations in AML, we found mutations in POLG , which is responsible for mitochondrial DNA replication 47 as well as mutations in MLH1 , which belongs to the DNA mismatch repair system and plays an important role in maintaining genomic stability 48–52 . Whereas both mutations were described to increase the risk of hereditary and sporadic cancers, 48,50,52,53 their incidence and clinical impact in AML are less well defined.…”
Section: Discussionmentioning
confidence: 88%